Shape and build - Read, Leon; Crawford, Andy (London Franklin Watts, 2007)
First non-fiction books introducing basic skills and concepts in a fun and engaging way, written in line with the Early Years Foundation Stage framework
Scientific notions
1
Keywords: Water -- Juvenile literature; Water